A method for preparing rare earth magnesium-based composite material

The method of semi-solid stirring and ultrasonic assisted dilution, followed by extrusion deformation, effectively addresses the challenge of preparing high-strength and high-elastic modulus magnesium alloy composites by ensuring uniform SiCp distribution and refining grain structure, significantly improving mechanical properties.

CN116790932BActive Publication Date: 2024-12-24TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310751589.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-24
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The challenge lies in preparing high-strength and high-elastic modulus magnesium alloy composite materials with uniform particle distribution, as traditional methods face difficulties in achieving this due to the narrow semi-solid range of rare earth elements, leading to issues like surface agglomeration and non-uniform distribution of reinforcement phases.

Method used

A method involving semi-solid stirring combined with liquid ultrasonic assisted dilution and subsequent extrusion deformation is employed to prepare a rare earth magnesium-based composite material, using SiCp reinforcement and controlled parameters to achieve uniform dispersion and improved mechanical properties.

Benefits of technology

The method results in a composite material with enhanced mechanical properties, including a strength increase of 163% compared to cast materials, with uniform SiCp distribution and refined grain structure, achieved through the combination of semi-solid stirring, ultrasonic dispersion, and extrusion processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116790932B_ABST
    Figure CN116790932B_ABST
Patent Text Reader

Abstract

A method for preparing a rare earth magnesium-based composite material belongs to the technical field of magnesium-based composite materials. Aiming at the narrow semi-solid interval of rare earth magnesium alloy, the technical problem of preparing high-strength and high elastic modulus magnesium alloy composite materials is solved. The solution is: Mg-7Gd-2Y-3Zn alloy is selected as the matrix, SiCp is the reinforcing phase, and the rare earth magnesium-based composite material is prepared by the method of semi-solid stirring + liquid ultrasonic assisted dilution. By regulating the stirring temperature, stirring speed and stirring time, a rare earth magnesium-based composite material with uniform SiCp distribution and no obvious agglomeration on the grain surface is obtained, and on this basis, the grains are further refined by an extrusion deformation process to improve the mechanical properties of the material. The yield strength of the rare earth magnesium-based composite material prepared by the present invention is 340.6MPa, and the tensile strength is 354.4MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium-based composite materials, and specifically relates to a preparation method of a rare earth magnesium-based composite material. Background Art

[0002] Magnesium alloys have the advantages of low density, high specific strength, and high specific stiffness, and are widely used in the automotive, aviation, aerospace, 3C and other industries. The room temperature tensile strength of magnesium alloys can reach more than 400MPa, and the elastic modulus is 45GPa, showing a significant strength-elastic modulus mismatch, which causes magnesium alloy parts to undergo significant elastic deformation under high stress service conditions, seriously affecting the service effect. Therefore, the development of magnesium alloys with high elastic modulus is of great significance.

[0003] Rare earth magnesium alloys have excellent room temperature and high temperature mechanical properties, high elastic modulus and creep resistance. Although rare earth magnesium alloys have many of the above advantages, the contribution of rare earth elements to the elastic modulus has reached a bottleneck, generally not exceeding 50GPa-55GPa. Moreover, the addition of a large amount of rare earth elements will cause the density of magnesium alloys to be high, which is contrary to its lightweight advantage. Rare earth magnesium alloy composite is another common method to improve the elastic modulus of magnesium alloys. Adding SiCp reinforcement phase to prepare rare earth magnesium-based composite materials can further improve the elastic modulus and strength of the alloy. However, due to the narrow semi-solid range of rare earth elements, it is difficult to obtain composite materials with uniform particle distribution using traditional semi-solid stirring casting methods. Therefore, in order to meet the urgent demand for high modulus and high-strength magnesium alloy materials in scientific and technological development, it is necessary to develop a new preparation process for rare earth magnesium-based composite materials. Summary of the invention

[0004] The main purpose of the present invention is to solve the technical problem of preparing high-strength and high elastic modulus magnesium alloy composite materials in view of the narrow semi-solid range of rare earth magnesium alloys. The present invention provides a method for preparing rare earth magnesium-based composite materials.

[0005] The design concept of the present invention is:

[0006] On the one hand, improvements were made based on the traditional semi-solid stirring, and a rare earth magnesium-based composite material with uniform SiCp dispersion and no obvious surface agglomeration was successfully prepared by semi-solid stirring + liquid ultrasonic assisted dilution method;

[0007] On the other hand, the present invention improves the mechanical properties of the alloy through the extrusion process. Extrusion is an effective deformation method to improve the structure and performance of cast magnesium alloys. Because the material is subjected to strong three-dimensional compressive stress during extrusion deformation, it can significantly eliminate casting defects, refine the structure, and facilitate the plastic deformation of the billet. Therefore, the extrusion forming process is very important for controlling the structure and performance of magnesium alloys.

[0008] In summary, the present invention selects Mg-7Gd-2Y-3Zn alloy as the matrix and SiCp as the reinforcement, the particle size of SiCp is 10um, and the preparation method is: semi-solid stirring + liquid ultrasonic assisted dilution process, and the stirring temperature, stirring speed and stirring time are controlled to obtain a rare earth magnesium-based composite material with uniform SiCp distribution and excellent performance.

[0009] The technical solution adopted by the present invention is: a method for preparing a rare earth magnesium-based composite material, comprising the following steps:

[0010] S1. SiCp pretreatment: SiCp powder is successively HF pickled, water washed, dried and sieved for later use;

[0011] S2. Raw material selection: weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloys and magnesium-yttrium master alloys, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; the weighed block raw materials are polished to remove the oxide scale on the surface, and wrapped with plastic wrap for use in the next step;

[0012] S3, put the clean crucible into the melting furnace for preheating, take it out after the clean crucible is preheated to 450℃~550℃, and evenly apply the coating agent on the inner wall of the crucible to prevent rust and other impurities from falling off the inner wall of the crucible;

[0013] S4, heating the smelting furnace to 730°C-750°C, and after the surface of the crucible turns yellow, placing the magnesium block prepared in step S2 into the crucible, and keeping the smelting furnace warm until the magnesium block is completely melted, and continuously introducing protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid;

[0014] S5, the smelting furnace is cooled to 710°C-720°C, the oxide layer on the surface of the magnesium liquid is removed, the zinc particles prepared in step S2 are added to the magnesium liquid and stirred for 0.5min-1.5min, and then kept warm for 10min-20min;

[0015] S6. First, put the SiCp powder pretreated in step S1 into a crucible wrapped in aluminum foil (the crucible is made of stainless steel), and put it into a drying furnace for preheating, and the preheating temperature is 600°C~620°C; then, when the alloy liquid obtained in step S5 is cooled to a semi-solid state with the furnace, that is, when the temperature of the melt is 610°C~630°C, remove the oxide layer on the surface of the alloy liquid, place a stirring paddle in the melt, start the stirring device for mechanical stirring, and the stirring time is 3min~5min; finally, after the semi-solid alloy melt forms a stable vortex, add the preheated SiCp into the semi-solid alloy melt, the added amount of SiCp powder accounts for 5% of the volume fraction of the total melt, stir for 10min~20min, and then withdraw the stirring paddle;

[0016] S7, the melting furnace is heated up to 680°C-700°C again, the oxide layer on the surface of the semi-solid alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy prepared in step S2 are placed into the semi-solid alloy melt, and after the solid alloy is melted, a stirring paddle is placed again for mechanical stirring;

[0017] S8. First, preheat the ultrasonic working rod to 480℃~500℃. At the same time, the melting furnace continues to heat up to 710℃~730℃ and then remove the stirring paddle. The stirring paddle continues to stir during the heating process of the melting furnace. Then, remove the oxide layer on the surface of the alloy liquid. Finally, extend the preheated ultrasonic working rod to 20mm below the alloy liquid surface. After ultrasonic dispersion for 10min~20min, take out the ultrasonic working rod and keep it warm for 5min~15min.

[0018] S9, first, preheat the casting mold to 400°C~500°C; then, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8; finally, cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 450KN, the pressure holding time is 180s~240s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a rare earth magnesium-based composite material ingot;

[0019] S10, cutting the ingot obtained in step S9 into a plurality of extruded blocks, then polishing the surface of the extruded blocks and sealing and preserving them for use in the next step;

[0020] S11, extrusion forming: first, preheat the extrusion die and the extrusion block saved in step S10 to 360°C respectively; then, place the extrusion block in the extrusion die, and use a press to hot extrude the extrusion block, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1 to obtain a rare earth magnesium-based composite material.

[0021] Further, in step S1, the SiCp pretreatment includes the following steps:

[0022] S1-1. Wash SiCp repeatedly with distilled water for at least three times, take out the washed SiCp and add sufficient HF for acid washing, stir and let stand;

[0023] S1-2, clean the SiCp after HF pickling with distilled water until the cleaning solution becomes neutral;

[0024] S1-3, spreading the SiCp cleaned in step S1-2 on a baking tray and drying it at a temperature of 80°C-100°C for a drying time of not less than 24 hours;

[0025] S1-4, the SiCp dried in step S1-3 is dispersed in an ultrasonic vibration screen and passed through a sieve with a pore size of 20 μm. The sieved SiCp is sealed and stored in a drying dish for use in the next step.

[0026] Furthermore, in step S2, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%.

[0027] Furthermore, in step S3, the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water.

[0028] Furthermore, in step S4, the protective gas is a mixed gas consisting of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1.

[0029] Furthermore, in the steps S5-S9, a slag scraper is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scraper is coated with a coating agent.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention prepares a composite material with uniform SiCp dispersion and no obvious agglomeration on the grain surface by a method of semi-solid stirring + liquid ultrasonic assisted dilution, and further improves the structure of the composite material by an extrusion deformation process. After extrusion, the number of recrystallized grains of the magnesium alloy is significantly increased, the grain size is small and uniform, and the mechanical properties of the composite material are improved. After extrusion treatment, the strength of the composite material is 354.4MPa, and the mechanical properties of the composite material are improved by 163% compared with the cast composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1The temperature and time relationship curve for preparing SiCp / Mg-7Gd-2Y-3Zn composite material;

[0033] Figure 2 The microstructure morphology of the prepared cast SiCp / Mg-7Gd-2Y-3Zn composite material;

[0034] Figure 3 The microstructure morphology of the prepared extruded SiCp / Mg-7Gd-2Y-3Zn composite material;

[0035] Figure 4 Comparison of stress-strain curves of prepared cast and extruded SiCp / Mg-7Gd-2Y-3Zn composite materials. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1

[0037] like Figure 1 A method for preparing a rare earth magnesium-based composite material is shown, comprising the following steps:

[0038] S1. SiCp pretreatment: SiCp pretreatment specifically includes the following steps:

[0039] S1-1. Use distilled water to repeatedly wash SiCp (particle size 10 μm) for at least three times, take out the washed SiCp and add sufficient HF for acid washing, stir and let stand;

[0040] S1-2, clean the SiCp after HF pickling with distilled water until the cleaning solution becomes neutral;

[0041] S1-3, spreading the SiCp cleaned in step S1-2 on a baking tray and drying it at a temperature of 80° C. for 24 hours;

[0042] S1-4, the SiCp dried in step S1-3 is dispersed in an ultrasonic vibration screen and then passed through a sieve with a pore size of 20 μm. The sieved SiCp is sealed and stored in a drying dish for use in the next step;

[0043] S2. Raw material selection: the purity of magnesium block is 99.9%, the purity of zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, the purity of magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, the purity of magnesium-yttrium master alloy is 99.9%,

[0044] Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloys and magnesium-yttrium master alloys, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; grind the weighed block raw materials to remove the oxide scale on the surface, and wrap them with plastic wrap for later use;

[0045] S3, putting a clean crucible into a smelting furnace for preheating, taking out the clean crucible after it is preheated to 450°C, and evenly applying a coating agent to the inner wall of the crucible, wherein the coating agent is composed of a talcum powder coating and a zinc oxide coating, and the ratio of the talcum powder coating is: 80g of talcum powder, 20g of water glass and 250ml of water; the ratio of the zinc oxide coating is: 45g of zinc oxide, 45g of water glass and 250ml of water;

[0046] S4, heating the smelting furnace to 730°C, and after the surface of the crucible turns yellow, placing the magnesium block prepared in step S2 into the crucible, and keeping the smelting furnace warm until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0047] S5, cooling the smelting furnace to 710°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles prepared in step S2 into the magnesium liquid and stirring for 0.5min, and then keeping the temperature for 10min;

[0048] S6. First, put the SiCp powder pretreated in step S1 into a crucible wrapped in aluminum foil (the crucible is made of stainless steel), and put it into a drying furnace for preheating at a temperature of 600°C; then, when the alloy liquid obtained in step S5 is cooled to a semi-solid state with the furnace, that is, when the temperature of the melt is 610°C, remove the oxide layer on the surface of the alloy liquid, place a stirring paddle in the melt, start the stirring device for mechanical stirring, and the stirring time is 3 minutes; finally, after the semi-solid alloy melt forms a stable vortex, add the preheated SiCp into the semi-solid alloy melt, the added amount of SiCp accounts for 5% of the volume fraction of the total melt, and remove the stirring paddle after stirring for 10 minutes;

[0049] S7, the melting furnace is heated up to 680°C again, the oxide layer on the surface of the semi-solid alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy prepared in step S2 are placed into the semi-solid alloy melt, and after the solid alloy is melted, a stirring paddle is placed again for mechanical stirring;

[0050] S8. First, preheat the ultrasonic working rod to 480°C. At the same time, the melting furnace continues to heat up to 710°C and then the stirring paddle is withdrawn. The stirring paddle continues to stir during the heating process of the melting furnace. Then, remove the oxide layer on the surface of the alloy liquid. Finally, extend the preheated ultrasonic working rod to 20mm below the alloy liquid surface. After 10 minutes of ultrasonic dispersion, take out the ultrasonic working rod and keep it warm for 5 minutes.

[0051] S9, first, preheat the casting mold to 400 ° C; then, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8; finally, cast the alloy liquid into the preheated casting mold, and use a press to die-cast with a pressure of 450KN and a holding time of 180s. After the die-casting is completed, take out the ingot and naturally cool it to room temperature to obtain a rare earth magnesium-based composite ingot. The microstructure morphology of the cast SiCp / Mg-7Gd-2Y-3Zn composite material is shown in the figure. Figure 2 As shown by Figure 2 It can be seen that the particles in the as-cast composite material are evenly dispersed, without obvious agglomeration and oxidation slag inclusions, SiCp is distributed in a necklace shape along the grain boundary, and the second phase is distributed in a discontinuous network along the grain boundary;

[0052] S10, cutting the ingot obtained in step S9 into a plurality of extruded blocks, then polishing the surface of the extruded blocks and sealing and preserving them for use in the next step;

[0053] S11, extrusion forming: First, the extrusion die and the extrusion block saved in step S10 are preheated to 360°C respectively; then, the extrusion block is placed in the extrusion die, and the extrusion block is hot extruded by a press, the extrusion rate is 0.1 mm / s, the extrusion temperature is 360°C, and the extrusion ratio is 16:1, to obtain a rare earth magnesium-based composite material. The microstructure morphology of the extruded SiCp / Mg-7Gd-2Y-3Zn composite material is shown in Figure 3 Shown by Figure 3 It can be seen that after extrusion, SiCp and the second phase are distributed along the extrusion direction, obvious dynamic recrystallization occurs in the matrix, and the grain size is significantly refined compared with the cast composite material.

[0054] Furthermore, in the steps S5-S9, a slag scraper is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scraper is coated with a coating agent.

[0055] Depend on Figure 4 It can be seen that the yield strength, tensile strength and elongation of the cast composite material are 99.0MPa, 134.5MPa and 0.93% respectively. After extrusion, the performance of the composite material is significantly improved, and the yield strength, tensile strength and elongation are increased to 340.6MPa, 354.4MPa and 1.82% respectively. Example 2

[0056] A method for preparing a rare earth magnesium-based composite material comprises the following steps:

[0057] S1. SiCp pretreatment: SiCp pretreatment specifically includes the following steps:

[0058] S1-1. Use distilled water to repeatedly wash SiCp (particle size 10 μm) for at least three times, take out the washed SiCp and add sufficient HF for acid washing, stir and let stand;

[0059] S1-2, clean the SiCp after HF pickling with distilled water until the cleaning solution becomes neutral;

[0060] S1-3, spreading the SiCp cleaned in step S1-2 on a baking tray and drying it at a temperature of 90° C. for 24 hours;

[0061] S1-4, the SiCp dried in step S1-3 is dispersed in an ultrasonic vibration screen and then passed through a sieve with a pore size of 20 μm. The sieved SiCp is sealed and stored in a drying dish for use in the next step;

[0062] S2. Raw material selection: the purity of magnesium block is 99.9%, the purity of zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, the purity of magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, the purity of magnesium-yttrium master alloy is 99.9%,

[0063] Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloys and magnesium-yttrium master alloys, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; grind the weighed block raw materials to remove the oxide scale on the surface, and wrap them with plastic wrap for later use;

[0064] S3, put the clean crucible into the smelting furnace for preheating, take out the clean crucible after it is preheated to 500°C, and evenly apply a coating agent on the inner wall of the crucible, wherein the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water;

[0065] S4, heating the smelting furnace to 740°C, and after the surface of the crucible turns yellow, placing the magnesium block prepared in step S2 into the crucible, and keeping the smelting furnace warm until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0066] S5, cooling the smelting furnace to 715°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles prepared in step S2 into the magnesium liquid and stirring for 1 minute, and then keeping the temperature for 15 minutes;

[0067] S6. First, put the SiCp powder pretreated in step S1 into a crucible wrapped in aluminum foil (the crucible is made of stainless steel), and put it into a drying furnace for preheating at a temperature of 610°C; then, when the alloy liquid obtained in step S5 is cooled to a semi-solid state with the furnace, that is, when the temperature of the melt is 620°C, remove the oxide layer on the surface of the alloy liquid, place a stirring paddle in the melt, start the stirring device for mechanical stirring, and the stirring time is 4 minutes; finally, after the semi-solid alloy melt forms a stable vortex, add the preheated SiCp into the semi-solid alloy melt, the added amount of SiCp accounts for 5% of the volume fraction of the total melt, and remove the stirring paddle after stirring for 15 minutes;

[0068] S7, the melting furnace is heated up to 690° C. again, the oxide layer on the surface of the semi-solid alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy prepared in step S2 are placed into the semi-solid alloy melt, and after the solid alloy is melted, a stirring paddle is placed again for mechanical stirring;

[0069] S8. First, preheat the ultrasonic working rod to 490°C. At the same time, the smelting furnace continues to heat up to 720°C and then the stirring paddle is withdrawn. The stirring paddle continues to stir during the heating process of the smelting furnace. Then, remove the oxide layer on the surface of the alloy liquid. Finally, extend the preheated ultrasonic working rod to 20mm below the alloy liquid surface. After 15 minutes of ultrasonic dispersion, take out the ultrasonic working rod and keep it warm for 10 minutes.

[0070] S9, first, preheat the casting mold to 450°C; then, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8; finally, cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 450KN, the holding time is 210s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a rare earth magnesium-based composite material ingot; in the steps S5-S9, use a slag scoop to remove the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scoop is coated with a coating agent;

[0071] S10, cutting the ingot obtained in step S9 into a plurality of extruded blocks, then polishing the surface of the extruded blocks and sealing and preserving them for use in the next step;

[0072] S11, extrusion forming: first, preheat the extrusion die and the extrusion block saved in step S10 to 360°C respectively; then, place the extrusion block in the extrusion die, and use a press to hot extrude the extrusion block, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1 to obtain a rare earth magnesium-based composite material. Example 3

[0073] A method for preparing a rare earth magnesium-based composite material comprises the following steps:

[0074] S1. SiCp pretreatment: SiCp pretreatment specifically includes the following steps:

[0075] S1-1. Use distilled water to repeatedly wash SiCp (particle size 10 μm) for at least three times, take out the washed SiCp and add sufficient HF for acid washing, stir and let stand;

[0076] S1-2, clean the SiCp after HF pickling with distilled water until the cleaning solution becomes neutral;

[0077] S1-3, spreading the SiCp cleaned in step S1-2 on a baking tray and drying it at a temperature of 100° C. for 24 hours;

[0078] S1-4, the SiCp dried in step S1-3 is dispersed in an ultrasonic vibration screen and then passed through a sieve with a pore size of 20 μm. The sieved SiCp is sealed and stored in a drying dish for use in the next step;

[0079] S2. Raw material selection: the purity of magnesium block is 99.9%, the purity of zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, the purity of magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, the purity of magnesium-yttrium master alloy is 99.9%,

[0080] Weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloys and magnesium-yttrium master alloys, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; grind the weighed block raw materials to remove the oxide scale on the surface, and wrap them with plastic wrap for later use;

[0081] S3, put the clean crucible into the smelting furnace for preheating, take out the clean crucible after it is preheated to 550°C, and evenly apply a coating agent on the inner wall of the crucible, wherein the coating agent is composed of talcum powder coating and zinc oxide coating, and the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water;

[0082] S4, heating the smelting furnace to 750°C, and after the surface of the crucible turns yellow, placing the magnesium block prepared in step S2 into the crucible, and keeping the smelting furnace warm until the magnesium block is completely melted, and continuously introducing a protective gas into the smelting furnace during the melting of the magnesium block to obtain magnesium liquid; the protective gas is a mixed gas composed of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:1;

[0083] S5, cooling the smelting furnace to 720°C, removing the oxide layer on the surface of the magnesium liquid, adding the zinc particles prepared in step S2 into the magnesium liquid and stirring for 1.5 minutes, and then keeping the temperature for 20 minutes;

[0084] S6. First, put the SiCp powder pretreated in step S1 into a crucible wrapped in aluminum foil (the crucible is made of stainless steel), and put it into a drying furnace for preheating at a temperature of 620°C; then, when the alloy liquid obtained in step S5 is cooled to a semi-solid state with the furnace, that is, when the temperature of the melt is 630°C, remove the oxide layer on the surface of the alloy liquid, place a stirring paddle in the melt, start the stirring device for mechanical stirring, and the stirring time is 5 minutes; finally, after the semi-solid alloy melt forms a stable vortex, add the preheated SiCp into the semi-solid alloy melt, the added amount of SiCp accounts for 5% of the volume fraction of the total melt, and remove the stirring paddle after stirring for 20 minutes;

[0085] S7, the melting furnace is heated to 700° C. again, the oxide layer on the surface of the semi-solid alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy prepared in step S2 are placed into the semi-solid alloy melt, and after the solid alloy is melted, a stirring paddle is placed again for mechanical stirring;

[0086] S8. First, preheat the ultrasonic working rod to 500°C. At the same time, the melting furnace continues to heat up to 730°C and then the stirring paddle is withdrawn. The stirring paddle continues to stir during the heating process of the melting furnace. Then, remove the oxide layer on the surface of the alloy liquid. Finally, extend the preheated ultrasonic working rod to 20mm below the alloy liquid surface. After ultrasonic dispersion for 20 minutes, take out the ultrasonic working rod and keep it warm for 15 minutes.

[0087] S9, first, preheat the casting mold to 500°C; then, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8; finally, cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 450KN, the pressure holding time is 240s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a rare earth magnesium-based composite material ingot; in the steps S5-S9, use a slag scoop to remove the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scoop is coated with a coating agent;

[0088] S10, cutting the ingot obtained in step S9 into a plurality of extruded blocks, then polishing the surface of the extruded blocks and sealing and preserving them for use in the next step;

[0089] S11, extrusion forming: first, preheat the extrusion die and the extrusion block saved in step S10 to 360°C respectively; then, place the extrusion block in the extrusion die, and use a press to hot extrude the extrusion block, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1 to obtain a rare earth magnesium-based composite material.

[0090] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a rare earth magnesium-based composite material, characterized in that: The following steps are involved: S1. SiCp pretreatment: SiCp powder is successively HF pickled, water washed, dried and sieved for later use; S2. Raw material selection: weigh magnesium blocks, zinc particles, magnesium-gadolinium master alloys and magnesium-yttrium master alloys, so that the composition and mass percentage of each element in the raw materials are: zinc: 3wt.%, gadolinium: 7wt.%, yttrium: 2wt.%, and the rest is magnesium; the weighed block raw materials are polished to remove the oxide scale on the surface, and wrapped with plastic wrap for use in the next step; S3, putting the clean crucible into the melting furnace for preheating, taking out the clean crucible after it is preheated to 450°C~550°C, and evenly applying the coating agent on the inner wall of the crucible; S4, heating the smelting furnace to 730°C-750°C, and after the surface of the crucible turns yellow, placing the magnesium block prepared in step S2 into the crucible, and keeping the smelting furnace warm until the magnesium block is completely melted, and continuously introducing protective gas into the smelting furnace during the melting process of the magnesium block to obtain magnesium liquid; S5, the smelting furnace is cooled to 710°C-720°C, the oxide layer on the surface of the magnesium liquid is removed, the zinc particles prepared in step S2 are added to the magnesium liquid and stirred for 0.5min-1.5min, and then kept warm for 10min-20min; S6. First, put the SiCp powder pretreated in step S1 into a crucible wrapped in aluminum foil, and put it into a drying furnace for preheating at a temperature of 600°C to 620°C; then, when the alloy liquid obtained in step S5 is cooled to a semi-solid state with the furnace, that is, when the temperature of the melt is 610°C to 630°C, remove the oxide layer on the surface of the alloy liquid, place a stirring paddle in the melt, start the stirring device for mechanical stirring, and the stirring time is 3min to 5min; finally, after the semi-solid alloy melt forms a stable vortex, add the preheated SiCp into the semi-solid alloy melt, the added amount of SiCp powder accounts for 5% of the volume fraction of the total melt, stir for 10min to 20min, and then withdraw the stirring paddle; S7, the melting furnace is heated up to 680°C-700°C again, the oxide layer on the surface of the semi-solid alloy melt is removed, and then the magnesium-gadolinium master alloy and the magnesium-yttrium master alloy prepared in step S2 are placed into the semi-solid alloy melt, and after the solid alloy is melted, a stirring paddle is placed again for mechanical stirring; S8. First, preheat the ultrasonic working rod to 480℃~500℃. At the same time, the melting furnace continues to heat up to 710℃~730℃ and then remove the stirring paddle. The stirring paddle continues to stir during the heating process of the melting furnace. Then, remove the oxide layer on the surface of the alloy liquid. Finally, extend the preheated ultrasonic working rod to 20mm below the alloy liquid surface. After ultrasonic dispersion for 10min~20min, take out the ultrasonic working rod and keep it warm for 5min~15min. S9, first, preheat the casting mold to 400°C~500°C; then, remove the oxide layer on the surface of the alloy liquid after the ultrasonic dispersion treatment in step S8; finally, cast the alloy liquid into the preheated casting mold, and use a press to perform die casting, the pressure is 450KN, the pressure holding time is 180s~240s, after the die casting is completed, take out the ingot and naturally cool it to room temperature to obtain a rare earth magnesium-based composite material ingot; S10, cutting the ingot obtained in step S9 into a plurality of extruded blocks, then polishing the surface of the extruded blocks and sealing and preserving them for use in the next step; S11, extrusion forming: first, preheat the extrusion die and the extrusion block saved in step S10 to 360°C respectively; then, place the extrusion block in the extrusion die, and use a press to hot extrude the extrusion block, with an extrusion rate of 0.1 mm / s, an extrusion temperature of 360°C, and an extrusion ratio of 16:1 to obtain a rare earth magnesium-based composite material.

2. The method for preparing a rare earth magnesium-based composite material according to claim 1, characterized in that: In step S1, the SiCp pretreatment includes the following steps: S1-1. Wash SiCp repeatedly with distilled water for at least three times, take out the washed SiCp and add sufficient HF for acid washing, stir and let stand; S1-2, clean the SiCp after HF pickling with distilled water until the cleaning solution becomes neutral; S1-3, spreading the SiCp cleaned in step S1-2 on a baking tray and drying it at a temperature of 80°C-100°C for 24 hours; S1-4, the SiCp dried in step S1-3 is dispersed in an ultrasonic vibration screen and passed through a sieve with a pore size of 20 μm. The sieved SiCp is sealed and stored in a drying dish for later use.

3. The method for preparing a rare earth magnesium-based composite material according to claim 1, characterized in that: In the step S2, the purity of the magnesium block is 99.9%, the purity of the zinc particles is 99.9%; the magnesium-gadolinium master alloy is Mg-30Gd, and the purity of the magnesium-gadolinium master alloy is 99.9%; the magnesium-yttrium master alloy is Mg-30Y, and the purity of the magnesium-yttrium master alloy is 99.9%.

4. The method for preparing a rare earth magnesium-based composite material according to claim 1, characterized in that: In step S3, the coating agent is composed of talcum powder coating and zinc oxide coating, the ratio of the talcum powder coating is: 80g talcum powder, 20g water glass and 250ml water; the ratio of the zinc oxide coating is: 45g zinc oxide, 45g water glass and 250ml water.

5. The method for preparing a rare earth magnesium-based composite material according to claim 1, characterized in that: In step S4, the protective gas is a mixed gas consisting of CO2 and SF6, and the volume ratio of CO2 to SF6 is 99:

1.

6. The method for preparing a rare earth magnesium-based composite material according to claim 1, characterized in that: In the steps S5-S9, a slag scraper is used to scrape off the oxide layer on the surface of the semi-solid alloy melt or the alloy liquid, and the surface of the slag scraper is coated with a coating agent.

Citation Information

Patent Citations

  • Method for heat resistant rare earth-magnesium alloy engine pistons through squeezing and casting

    CN101693972A

  • Preparation method of double-size silicon carbide particle hybrid reinforced magnesium matrix composite material

    CN102943198A

  • Method for preparing novel magnesium-based composite by ultrasonic assisted mechanical mixing

    CN108085549A

  • Preparation method of corrosion-resistant silicon carbide particle reinforced magnesium-based composite board

    CN109898001A

  • High-volume-fraction multi-phase hybrid reinforced magnesium-based composite material and preparation method thereof

    CN112176262A